Digital Transformation in Family Businesses - Georg Streicher (Junior Management Science (JUMS), 2023)
Nowadays, the impact of digital technologies on all businesses is inescapable for their managers and is receiving a great deal of attention in research and businesses. Digitalization as an ongoing process has just begun and will continue to drive many decision-making processes. So far, much research has been done on technical implementations and digital technologies as such, but there is still a lack of research on the decision-making processes around digitalization, especially in small and medium-sized businesses with limited resources, such as the economically important family businesses (FBs) in Germany. These FBs have a massive impact on value creation in Germany and include many global market leaders. Based on eleven interviews with family and non-family member Chief Executive Officers (CEOs) and employees, the thesis shows which drivers and barriers exist in the digitalization process in FBs and how they influence the process. Moreover, their influence on the digitalization of the business model is examined. The results of the thesis provide implications for how FBs can successfully master digitalization and use it to their advantage. Finally, the thesis suggests opportunities for future research in digitalization in FBs and on identified correlations in the cases.
Keywords: 650; Digital transformation; Family business; Digitalization